Pharmacological evaluation of analgesic, anti-pyretic and anti-inflammatory activities of ethanolic root extract of Amaranthus caudatus - Kumar, Vivek; Monika, Km; Rathi, Bhawana; Agarwal, Ruchi; Khan, Najam Ali; Swain, Sudhansu Ranjan (Journal of Drug Delivery and Therapeutics, 2023)
Background: Amaranthus caudatus Linn, belonging to a family Amaranthaceae. Amaranthus caudatus is found in South America, India, or Indo-Chinese district, Mexico, and the Mediterranean area. Amaranthus caudatus contains different kinds of substance constituents which are responsible for its therapeutic potential. Amaranthus caudatus is usually utilized in the treatment of jaundice, amoebiasis, and kidney ailment, as a blood purifier, diuretic, abortifacient, vermifuge, astringents, and for liver illness. The research work deals with the screening of the analgesic, antipyretic and anti-inflammatory activities of ethanolic root extract of Amaranthus caudatus. For this, the alcoholic extract of the selected plant was used for analgesic activity, anti-inflammatory activity and anti-pyretic activities. The result: In current investigation, diclofenac sodium (10mg/kg, p.o.) was used as a standard drug. The effects of ethanolic root extract (200 and 400mg/kg, p.o.) of Amaranthus caudatus on Wistar albino rats for the assessment of analgesic, anti-inflammatory as well as antipyretic activities. The current research revealed that EEAC (200 and 400mg/kg,p.o.) possessed significant (P<0.05) analgesic, anti-inflammatory and antipyretics activities in a dose-dependent manner. Furthermore EEAC (200 and 400mg/kg p.o) were effective as standard drug (Diclofenac sodium 10mg/kg, p.o). All these methods were performed under highly supervised conditions and by proper handling of experimental animals having been granted permission by IAEC. The conclusion: In the present study, it was concluded that the EEAC was effective in a dose-dependent manner and possessed potent analgesic, anti-inflammatory and antipyretic activities. Keywords: Amaranthus caudatus, Analgesic, Anti-pyretic, Anti-inflammatory, Diclofenac sodium, Phytochemical screening.